Perbedaan Fonologi Bahasa Indonesia Dan Bahasa Inggris - Tri Nur Rizki Safitri; Aryanti Awaludini; Dio Purnama (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Structure is the arrangement or combination of language elements into a patterned language. Thus, phonology is the sound system in Indonesian or it can also be said that phonology is the science of language. This research aims to find similarities and differences between Indonesian and English phonetics. The method used in this article is qualitative descriptive because the researcher will explain descriptively the differences between Indonesian and English at the phonological level.